Diabetes and global ageing among 65–99-year-old adults: Findings from the International Diabetes Federation Diabetes Atlas, 9th edition. (April 2020) - Sinclair, Alan; Saeedi, Pouya; Kaundal, Abha; Karuranga, Suvi; Malanda, Belma; Williams, Rhys
Highlights: Globally, 1 in 5 people aged 65–99 years live with diabetes (136 million). NAC Region has the highest and AFR the lowest diabetes prevalence (65–99 years). China and the US have the highest number of 65–99-year-old adults with diabetes. Abstract: Aims: The main aims are: (a) to draw attention to the nature and pattern of recent global and regional prevalence estimates and projections of diabetes in older adults (65–99 years), and (b) to describe the societal health implications of these changes on a global scale. Methods: Diabetes prevalences and projections were estimated using a logistic regression method to generate smoothed age- and sex-specific prevalence estimates for 5-year age groups. Results: In 2019, it is estimated that 19.3% of people aged 65–99 years (135.6 million, 95% CI: 107.6–170.6 million) live with diabetes. It is projected that the number of people older than 65 years (65–99 years) with diabetes will reach 195.2 million by 2030 and 276.2 million by 2045. For the regional distribution, the highest prevalence in 2019 being the North America and Caribbean Region at 27.0%. Countries with the highest number of people older than 65 years with diabetes are China, the United States of America and India. Conclusions: There is a need for more data from national and regional sources on those aged 65 years and over, but the prevailing evidence points to diabetes being a considerable global chronic illness burden in ageing societies.